Reductive Electrophilic Cross-Coupling for Constructing C(sp3)–C(sp3) Bonds - Li, Pengfei; Qiu, Youai (Synlett, 2024)
The C(sp3)–C(sp3) bond is one of the most prevalent motifs in organic compounds and holds significant importance in organic synthesis. The utilization of two alkyl electrophiles for cross-coupling stands as a vital strategy in building C(sp3)–C(sp3) bonds. Nowadays, synthetic electrochemistry is undergoing rapid development owing to its exceptional attributes not only in terms of green and economic properties by reducing the large amount of traditional chemical reductants, but also by its capacity to generate highly reactive radical intermediates under mild conditions, thereby opening up new reaction pathways and presenting novel opportunities to constructing C(sp3)–C(sp3) bonds. This article aims to comprehensively delineate the historical development of traditional electrophilic reagents in constructing C(sp3)–C(sp3) bonds, while also delving into the advantages of electrochemical electrophilic cross-coupling in this domain.1 Introduction2 Case Studies of Nickel-Catalyzed and Photochemical Alkyl Halide Cross-Coupling3 Case Studies of Electrocatalyzed Approaches for the Construction of C(sp3)–C(sp3) Bonds Using Electrophilic Reagents4 Nickel-Electrocatalyzed C(sp3)–C(sp3) Cross-Coupling of Unactivated Alkyl Halides5 Conclusion
Keywords: electrophilic reagents; cross-coupling; organic electrosynthesis; C(sp3)–C(sp3) bonds; nickel catalysis